A Suggested New Material to Manufacture Above-Knee Prosthetic Socket Using the Lamination of Monofilament, Cotton and Perlon Fibers - Chiad, Jumaa S.; Tahir, Muhammad Safa al-Din (Al-Nahrain Journal for Engineering Sciences, 2017)
thetic socket, is due to its fiber strength and hardness, and low cost, but there are other more important things which must be considered than these specifications which are1the health1and safety. In this research fiberglass is replaced with monofilament fiber in order to be safe to on makers and users of this socket. In this paper two models of lamination manufacturing have been made and compared in terms of mechanical properties and fatigue life. The first is available and consists of: (4 perlon, 2 fiberglass and 4 perlon), The second is proposed lamination which consists of: (4 perlon, 1 cotton, 1 monofilament and 4 perlon). Simulations were conducted on the made socket made of two types of lamination by using ANSYS 14.5 to show the distribution of stresses, the amount of deformation and less safety factor for both cases. The results show an increase of 42% in the Young’s modulus and a decrease in tensile stress and yield stress by 10.8% and 46% respectivel, As for the stress endurance it witnessed an increase of 140%.The simulation results show a decrease in the deformation by 40.7% and an increase in the minimum value of the safety factor of 0.323 to 1.05.